Transabdominal chorionic villus sampling: Experience at Maharaj Nakorn Chiang Mai Hospital - Supatra Sirichotiyakul (2018)
Objective: To describe the experience of transabdominal chorionic villus sampling (CVS) at Maharaj Nakorn Chiang Mai Hospital. Material and Method: Between January 2004 and July 2006, 185 pregnant women chose to have CVS for prenatal diagnosis after counseling. Transabdominal CVS under ultrasound guidance was performed in all cases under local anesthesia using spinal needle 20-gauge with back and forth movement technique. The sample was immediately examined under a microscope to determine if the villi were obtained and to remove the decidua (maternal cells) from the villi. Results: The mean gestational age was 12.25 ± 1.05 weeks (range 10-20 weeks). The procedure was successful in all cases, 168 cases (90.9%) with one attempt. The indications for prenatal diagnosis included fetal risk for chromosomal abnormalities (110 cases; 59.46%), severe thalassemia syndrome (57 cases; 30.81%), both of them (17 cases; 9.19%) and for HLA typing in one case. The results could not be obtained in 11 cases (5.95%) due to laboratory failure. In the present study, abnormal chromosomes were detected in chorionic villi from 12 fetuses, including 45,X (3), trisomy 18 (3), trisomy 21 (2), trisomy 7 (1) and mosaicism (3). Additionally, 18 fetuses with severe thalassemia syndrome were identified; five homozygous beta-thalassemia, 11 beta-thalas-semia/Hb E disease, and two homozygous alpha-thalassemia (Hb Bart's). The complications found in the present study included one case (0.54%) of fetal loss following the procedure and one case (0.54%) of vaginal bleeding. No case with limb reduction defect, infection, or rupture of membranes following the procedure was seen. Conclusions: Transabdominal CVS is a rather safe and reliable prenatal diagnostic technique. The fetal loss rate following the procedure in the present study was 0.54%. However, operator's experience and skill in ultrasound-directed needle guidance procedure are essential.